A cast power inductor and its preparation method

Through the preparation method of cast power inductors, the use of cast magnetic slurry pressureless molding and composite soft magnetic alloy powder solves the problem of coil damage caused by high inductor molding pressure, improves the reliability and production efficiency of the inductor, reduces costs, and is suitable for large-scale production of small-size inductors.

CN115064344BActive Publication Date: 2025-09-23HENGDIAN GRP DMEGC MAGNETICS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210728699.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-24
Publication Date
2025-09-23
Estimated Expiration
2042-06-24

AI Technical Summary

Technical Problem

In the prior art, the inductor molding pressure is high, which causes coil deformation, short circuit or open circuit. The molding equipment requirements are high, the production efficiency is low, the cost is high, and it is not suitable for large-scale production of small-sized inductors.

Method used

The cast power inductor is prepared by pouring magnetic slurry for pressureless molding to avoid short circuit and open circuit caused by excessive pressure on the coil. Composite soft magnetic alloy powder and hot pressing molding are used, combined with multi-stage curing treatment and precise cutting to improve product reliability and yield.

Benefits of technology

It realizes pressure-free forming, avoids coil damage, improves the reliability and production efficiency of the inductor, reduces production costs, and is suitable for large-scale production of small-size inductors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115064344B_ABST
    Figure CN115064344B_ABST
Patent Text Reader

Abstract

The present invention provides a cast power inductor, which includes a base, a hollow coil and a casting body; the base includes a hem and a center column; the center column is fixedly arranged at the center of the hem; the hollow coil is tightly wound on the center column; and the casting body is used to wrap the base and the hollow coil. The preparation method of the cast power inductor includes the following steps: blank preparation, coil winding, assembly arrangement, slurry pouring, curing treatment and post-treatment. The cast power inductor provided by the present invention realizes pressure-free forming by pouring magnetic slurry, which avoids the coil from short-circuiting, breaking or deviating to the edge of the inductor due to excessive pressure; effectively improves the reliability of the inductor and the yield rate of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electronic components and relates to a power inductor, in particular to a cast power inductor and a preparation method thereof. Background Art

[0002] With the rapid development of science and technology, the requirements for the performance and reliability of electronic products are becoming increasingly stringent. As one of the three major passive components in electronic circuits, inductors play a role in filtering, oscillating, filtering noise, stabilizing current, and suppressing electromagnetic interference. In today's era of rapid technological advancement, the current and frequency requirements for inductors are becoming increasingly higher. Traditional dry-pressed one-piece molded inductors require a high molding pressure, which can easily cause large deformation of the inductor's internal coil or damage the insulating paint on the copper wire surface, leading to open circuits and short circuits during the pressing process. In addition, the dry-pressing molding process has high requirements for molding equipment and molds. Due to the tonnage of the press and the mold design, the production efficiency of the product is limited, and the production cost of the inductor remains high.

[0003] Therefore, magnetic slurry casting molding is the focus of research. However, this process is to mix the magnetic material with glue to form a colloid with high viscosity, which leads to a lower solid content of the magnetic powder compared to compression molding, resulting in a low inductance value.

[0004] CN 213752214U discloses a cast inductor comprising a box body and a conductor coil. The box body is formed by pressing magnetic powder, the conductor coil is disposed within the box body, and the lead end of the conductor coil extends from the box body. Magnetic slurry is poured into the box body, and the magnetic slurry is flush with the opening edge of the box body. The box body, conductor coil, and magnetic slurry are integrally cast. The cast inductor provided by this patent is cast by casting, eliminating the need for pressing the coil, thus avoiding coil deformation and effectively preventing magnetic leakage. However, this utility model patent uses magnetic powder to first press the box body, and then separately arranges the coils within the box body and casts them. This process is complex and tedious, resulting in low production efficiency. When producing micro-sized inductors, the box body wall is relatively thin and easily damaged during assembly, making it unsuitable for large-scale production of small-sized inductors.

[0005] CN 112397295 A discloses a manufacturing method of an integrally formed inductor. The manufacturing method includes: first pre-pressing a soft magnetic alloy material into a flat blank and a T-shaped blank, then precisely winding enameled wire around the columnar protrusion of the T-shaped blank, and then placing the T-shaped blank wound with enameled wire in a hot pressing mold in an "丄" shape, and placing the prefabricated flat blank above the T-shaped blank for hot pressing to obtain an integrally formed inductor blank. Finally, spraying and electroplating electrodes on the inductor blank to obtain an integrally formed inductor. The manufacturing method provided by this patent only solves the problems that in the production of integrally formed inductors, due to the unevenness of prefabricated powder particles, there are large deviations in the amount of powder filled into each cavity of the mold during the forming stage, resulting in large size, weight and performance deviations in the pressed inductor blanks, and components such as enameled wire are already included in defective products, and it is difficult to recycle the powder. It still cannot avoid large deformations in the internal coil of the inductor during the die pressing process, or open circuit and short circuit phenomena due to the damage of the insulating paint on the surface of the enameled wire.

[0006] In summary, there is an urgent need in the art to provide an inductor and its preparation method to solve the technical problems in the prior art such as high required forming pressure, high requirements for forming equipment, and short circuit and open circuit caused by damage to copper wires due to excessive forming pressure. Summary of the Invention

[0007] The purpose of the present invention is to provide a casting type power inductor and its preparation method. The casting type power inductor realizes non-pressure forming by casting magnetic slurry, avoiding short circuit, open circuit or deviation of the coil to the edge of the inductor due to excessive pressure; effectively improving the reliability of the inductor and the yield of the product.

[0008] To achieve the purpose of this invention, the following technical solutions are adopted in this invention:

[0009] In the first aspect, the present invention provides a casting type power inductor, which includes a T-shaped base, a hollow coil and a casting body;

[0010] The base includes a lower swing and a middle column;

[0011] The middle column is fixedly arranged at the central position of the lower swing;

[0012] The hollow coil is tightly wound around the middle column;

[0013] The casting body is used to wrap the base and the hollow coil.

[0014] The casting type power inductor provided by the present invention solves the technical problems in the prior art such as high required forming pressure, high requirements for forming equipment, and short circuit and open circuit caused by damage to copper wires due to excessive forming pressure

[0015] Preferably, a wire groove is provided on one side of the hem.

[0016] Preferably, the pins at both ends of the hollow coil are arranged at the bottom of the hem through wire grooves.

[0017] In a second aspect, the present invention provides a method for preparing the cast power inductor provided in the first aspect, the method comprising the following steps:

[0018] (1) Blank preparation: The prefabricated powder is placed into a T-shaped mold of a preset size and hot-pressed, and then baked to obtain a T-shaped base;

[0019] (2) Winding the coil: Winding the enameled wire on the center column of the T-shaped base obtained in step (1), and bending the two end pins and attaching them to the bottom of the hem of the T-shaped base to obtain an assembly;

[0020] (3) Arrangement of the assembly: The assembly obtained in step (2) is arranged in an n×m matrix with equal spacing and pasted on a heat-sensitive adhesive film;

[0021] (4) Slurry casting: a casting mold is installed above the heat-sensitive adhesive film, and magnetic slurry is injected to obtain a second assembly;

[0022] (5) Curing treatment: curing, demolding and polishing the second assembly obtained in step (4) to obtain an inductor blank;

[0023] (6) Post-processing: Cutting, spraying, and electroplating the inductor blank obtained in step (5) in sequence to obtain the cast power inductor.

[0024] The preparation method of the cast power inductor provided by the present invention adopts a one-step molding process without pressure, which solves the technical problems of the prior art such as high molding pressure, high molding equipment requirements, and damage to the copper wire due to excessive molding pressure, resulting in short circuit and open circuit.

[0025] Preferably, the method for preparing the prefabricated powder in step (1) comprises:

[0026] (1.1) Mixing the main powder and the auxiliary powder to obtain composite soft magnetic alloy powder;

[0027] (1.2) Mixing a binder, a curing agent, acetone, and the composite soft magnetic alloy powder obtained in step (1.1) to obtain a prefabricated powder.

[0028] Preferably, the main powder in step (1.1) comprises any one or a combination of at least two of FeSiAl powder, FeSi powder or FeNi powder. Typical but non-limiting combinations include a combination of FeSiAl powder, FeSi powder and FeNi powder, a combination of FeSiAl powder and FeSi powder, a combination of FeSiAl powder and FeNi powder, or a combination of FeSi powder and FeNi powder.

[0029] Preferably, the D50 of the main powder in step (1.1) is 20-40 μm, for example, it can be 20 μm, 25 μm, 30 μm, 35 μm or 40 μm, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0030] Preferably, the auxiliary powder in step (1.1) comprises any one or a combination of at least two of FeSiAl powder, FeSi powder or FeNi powder. Typical but non-limiting combinations include a combination of FeSiAl powder, FeSi powder and FeNi powder, a combination of FeSiAl powder and FeSi powder, a combination of FeSiAl powder and FeNi powder, or a combination of FeSi powder and FeNi powder.

[0031] Preferably, the D50 of the auxiliary powder in step (1.1) is 2-10 μm, for example, it can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] The composition of the main powder and the auxiliary powder in the composite soft magnetic alloy powder described in step (1.1) of the present invention can be exactly the same, and the selection of materials depends on the specific application requirements. FeSiAl material has high hardness, saturation magnetic induction intensity Bs, magnetic permeability and resistivity, and low cost; the disadvantage is that the magnetic properties are sensitive to composition fluctuations, it is brittle, and the processing performance is poor. FeSi material has a higher saturation magnetic induction intensity than FeSiAl, has a higher energy storage capacity, and is suitable for high current working conditions. Compared with FeSiAl, FeNi has better DC superposition characteristics. Since the powder contains about 50% nickel, the material cost is relatively high.

[0033] Preferably, the temperature of the hot pressing molding in step (1) is 160-240°C, for example, it can be 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or 240°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] Preferably, the pressure of the hot pressing molding in step (1) is 300-600 MPa, for example, it can be 300 MPa, 350 MPa, 400 MPa, 450 MPa, 500 MPa, 550 MPa or 600 MPa, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0035] Preferably, the baking temperature in step (1) is 180-260°C, for example, it can be 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C or 260°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0036] The purpose of the hot pressing molding in the present invention is to ensure that the T-shaped blank can obtain good strength and prevent the center column on the T-shaped base from breaking during the preparation process of the winding coil.

[0037] Preferably, the spacing between the assembly bodies in step (3) is 0.5-2 mm, for example, it can be 0.5 mm, 0.8 mm, 1 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm or 2 mm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] The spacing between the assemblies is mainly to allow the casting body to be completely wrapped, thereby effectively ensuring the adhesion between the casting body and the assembly.

[0039] Preferably, the adhesion of the thermal adhesive in the thermal adhesive film in step (3) is 2000-3000 gf / 25mm, for example, it can be 2000 gf / 25mm, 2200 gf / 25mm, 2400 gf / 25mm, 2600 gf / 25mm, 2800 gf / 25mm or 3000 gf / 25mm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0040] The limited range of the adhesion of the thermal adhesive of the present invention is to ensure that the coil and the T-shaped base can be tightly adhered by the thermal adhesive.

[0041] Preferably, the viscosity of the magnetic slurry in step (4) is 15000-25000 mPa.s, for example, it can be 15000 mPa.s, 17000 mPa.s, 19000 mPa.s, 21000 mPa.s, 23000 mPa.s or 25000 mPa.s, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0042] The magnetic slurry in step (4) of the present invention has a magnetic permeability of 25-35 when the frequency is 100 kHz.

[0043] Preferably, the raw materials of the magnetic slurry in step (4) include, by weight: 100 parts of composite soft magnetic alloy material, 2-8 parts of epoxy resin, for example, it can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts or 8 parts, but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; 0.5-2.5 parts of curing agent, for example, it can be 0.5 parts, 0.8 parts, 1 part, 1.4 parts, 1.8 parts, 2.2 parts or 2.5 parts, but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; 2-6 parts of organic solvent, for example, it can be 2 parts, 3 parts, 4 parts, 5 parts or 6 parts, but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0044] The amount of epoxy resin added in the present invention is determined to balance a certain bond strength between the casting and the coil / T-shaped base assembly, while also ensuring a certain magnetic permeability of the casting after curing. If the epoxy resin is added in a small amount, the bonding strength between the casting and the assembly is reduced, leading to detachment. If the epoxy resin is added in an excessive amount, the magnetic permeability of the casting is reduced, and the inductor value does not meet the technical requirements.

[0045] Preferably, the curing agent comprises any one of ethylenediamine, diethylenetriamine, diethyltoluenediamine or dicyandiamide, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of ethylenediamine and diethylenetriamine, or a combination of diethyltoluenediamine and dicyandiamide.

[0046] Preferably, the organic solvent comprises any one or a combination of at least two of ethyl acetate, n-propanol, isopropanol or ethanol, and typical but non-limiting combinations include a combination of n-propanol and isopropanol, a combination of n-propanol and ethanol, or a combination of ethyl acetate and ethanol.

[0047] Preferably, the method for preparing the magnetic slurry in step (4) comprises:

[0048] (4.1) Mixing the epoxy resin and the organic solvent, stirring for 1-3 hours to obtain an organic mixture;

[0049] (4.2) adding the composite soft magnetic alloy material to the organic mixture obtained in step (4.1) and stirring for 4-12 hours to obtain a semi-finished soft magnetic alloy powder slurry;

[0050] (4.3) Mixing and stirring the curing agent and the semi-finished soft magnetic alloy powder slurry obtained in step (4.2) for 20-40 minutes, and then vacuum degassing to obtain the magnetic slurry.

[0051] Preferably, the composite soft magnetic alloy material in step (4.2) is a mixture of a first powder, a second powder and a third powder.

[0052] Preferably, the first powder comprises any one of FeSiAl powder, FeSi powder, FeNi powder or amorphous powder, or a combination of at least two thereof;

[0053] Preferably, the D50 of the first powder is 100-150 μm, for example, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] Preferably, the second powder comprises any one of FeSiAl powder, FeSi powder, FeNi powder or amorphous powder, or a combination of at least two thereof;

[0055] Preferably, the D50 of the second powder is 20-50 μm, for example, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] Preferably, the third powder comprises any one of FeSiAl powder, FeSi powder, FeNi or amorphous powder, or a combination of at least two thereof;

[0057] Preferably, the D50 of the third powder is 4-10 μm, for example, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] Preferably, the mass ratio of the first powder, the second powder and the third powder is 6:(1-3):(1-3), for example, it can be 6:1:1, 6:1:3, 6:3:1, 6:2:3, 6:3:3 or 6:3:2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] Preferably, the amorphous powder comprises FeSiBCr.

[0060] The composite soft magnetic alloy material described in the present invention is made by mixing a first powder (coarse powder), a second powder (medium powder) and a third powder (fine powder) with completely different particle sizes. Before mixing, the coarse, medium and fine powders need to be annealed at high temperatures to eliminate internal stress, which is beneficial to reducing hysteresis loss.

[0061] The coarse powder in the composite soft magnetic alloy material provided by the present invention is much larger in particle size than the powder used in the traditional molding process. The coarse, medium and fine powders are mixed and matched, and the medium and fine powder particles fully fill the gaps between the coarse powder particles, thereby increasing the filling density of the slurry and achieving a higher magnetic permeability of the cast body. This makes up for the problem of low magnetic permeability in the pressureless state. In addition, the slurry used in the cast body has a high epoxy resin content, which not only improves the strength of the product, but also can better insulate the soft magnetic alloy powder, increase its resistivity, and play a role in reducing eddy current losses.

[0062] Preferably, the height of the casting mold in step (4) is greater than 0.4-1.5 mm of the inductor height, and can be, for example, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.2 mm, 1.4 mm, or 1.5 mm, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable; preferably, it is 0.6-1.2 mm.

[0063] The mold height is required to be greater than the inductor height during the casting process of the present invention in order to reserve a shrinkage margin for the slurry and a margin for polishing after the cast body is solidified.

[0064] Preferably, the curing in step (5) includes first-stage curing, second-stage curing and third-stage curing performed sequentially.

[0065] The curing process described in the present invention utilizes a staged curing process, initially at a low temperature for a long time, followed by a gradual increase in temperature. This ensures that the epoxy resin is densely packed within the casting during curing and prevents the formation of voids. Because thermosetting epoxy resins cure faster at high temperatures, and curing is an exothermic reaction, curing in a short time can accelerate the curing process, which can easily lead to "boiling" and residual voids within the casting after curing, resulting in reduced magnetic permeability and strength.

[0066] Preferably, the temperature of the first stage curing is 80-100°C, for example, 80°C, 84°C, 88°C, 92°C, 96°C or 100°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] Preferably, the holding time for the first stage curing is 2-4h, for example, it can be 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3h, 3.2h, 3.4h, 3.6h, 3.8h or 4h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] Preferably, the temperature of the second stage curing is 120-140°C, for example, 120°C, 124°C, 128°C, 132°C, 136°C or 140°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0069] Preferably, the holding time for the second stage curing is 0.5-2h, for example, 0.5h, 0.8h, 1h, 1.2h, 1.4h, 1.6h, 1.8h or 2h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0070] Preferably, the temperature of the third stage curing is 150-200°C, for example, it can be 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C or 200°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] Preferably, the holding time for the third stage curing is 1-3 hours, for example, it can be 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours or 3 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0072] Preferably, step (6) further includes baking the sprayed material after the spraying.

[0073] The polishing in step (5) of the present invention can not only accurately control the height of the inductor, but also ensure that the surface of the casting body is smooth.

[0074] The cutting described in step (6) of the present invention is performed using a dicing machine or wire cutting. First, a UV film is applied to the surface of the cast body polished in step (5). The surface with the UV film is then placed on a workbench. The UV film and the polished inductor blank are fixed by a vacuum suction cup on the workbench. The polished inductor blank is divided into n×m inductor blanks by setting a starting mark and a moving distance of the workbench. The moving distance of the workbench is determined according to the length and width dimensions of the inductor product.

[0075] As a preferred technical solution of the present invention, the method for preparing the cast power inductor provided in the second aspect of the present invention comprises the following steps:

[0076] (1) Blank preparation: The prefabricated powder is placed into a T-shaped mold of a preset size and hot-pressed, and then baked at 180-260°C to obtain a T-shaped base; wherein the hot-pressing temperature is 160-240°C and the pressure is 300-600 MPa;

[0077] (1.1) mixing a main powder and an auxiliary powder to obtain a composite soft magnetic alloy powder; wherein the D50 of the main powder is 20-40 μm, and the D50 of the auxiliary powder is 2-10 μm;

[0078] (1.2) mixing a binder, a curing agent, acetone, and the composite soft magnetic alloy powder obtained in step (1.1) to obtain a prefabricated powder;

[0079] (2) Winding the coil: Winding the enameled wire on the center column of the T-shaped base obtained in step (1), and bending the two end pins and attaching them to the bottom of the hem of the T-shaped base to obtain an assembly;

[0080] (3) Arrangement of the assembly: The assembly obtained in step (2) is arranged in an n×m matrix with equal spacing and pasted on a heat-sensitive adhesive film with an adhesion of 2000-3000 gf / 25 mm; wherein the spacing between the assemblies is 0.5-2 mm;

[0081] (4) Slurry casting: a casting mold is installed above the thermal adhesive film, and a magnetic slurry with a viscosity of 15,000-25,000 mPa.s is injected to obtain a second assembly; wherein the height of the casting mold is 0.4-1.5 mm greater than the height of the inductor;

[0082] (4.1) Mixing the epoxy resin and the organic solvent, stirring for 1-3 hours to obtain an organic mixture;

[0083] (4.2) adding a composite soft magnetic alloy material to the organic mixture obtained in step (4.1), and stirring for 4-12 hours to obtain a semi-finished soft magnetic alloy powder slurry; wherein the composite soft magnetic alloy material is a mixture of a first powder, a second powder, and a third powder; the D50 of the first powder is 100-150 μm, the D50 of the second powder is 20-50 μm, and the D50 of the third powder is 4-10 μm;

[0084] (4.3) mixing and stirring the curing agent and the semi-finished soft magnetic alloy powder slurry obtained in step (4.2) for 20-40 minutes, and then vacuum degassing to obtain the magnetic slurry;

[0085] (5) Curing treatment: The second assembly obtained in step (4) is cured, demolded, and polished in sequence to obtain an inductor blank; wherein the curing treatment includes first-stage curing, second-stage curing, and third-stage curing in sequence; the temperature of the first-stage curing is 80-100°C, and the holding time is 2-4 hours; the temperature of the second-stage curing is 120-140°C, and the holding time is 0.5-2 hours; the temperature of the third-stage curing is 150-200°C, and the holding time is 1-3 hours;

[0086] (6) Post-processing: Cutting, spraying, and electroplating the inductor blank obtained in step (5) in sequence to obtain the cast power inductor.

[0087] The numerical range described in the present invention includes not only the point values ​​listed above, but also any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0088] Compared with the prior art, the present invention has the following beneficial effects:

[0089] The cast power inductor provided by the present invention is formed without pressure by pouring magnetic slurry, thereby preventing the coil from short-circuiting, breaking or deviating to the edge of the inductor due to excessive pressure, thereby effectively improving the reliability of the inductor and the yield rate of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0090] Figure 1 A schematic structural diagram of a cast power inductor provided in Example 1 of the present invention;

[0091] Figure 2 A side cross-sectional view of the cast power inductor provided in Example 1 of the present invention;

[0092] Figure 3 This is a schematic structural diagram of the inductor body provided in Example 1 of the present invention.

[0093] Among them, 1 is a T-shaped base, 2 is a hollow coil, 3 is a cast body, 4 is a center column, and 13 is a wire trough. DETAILED DESCRIPTION

[0094] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0095] Example 1

[0096] This embodiment provides a Figure 1 The cast power inductor shown includes a T-shaped base 1, an air-core coil 2, and a cast body 3;

[0097] The T-shaped base 1 includes a hem and a center column 4; the center column 4 is fixedly arranged at the center position of the hem; the hollow coil 2 is tightly wound on the center column 4; the cast body 3 is used to wrap the T-shaped base 1 and the hollow coil 2.

[0098] A wire groove 13 is provided on one side of the hem; the pins at both ends of the hollow coil 2 are arranged at the bottom of the hem through the wire groove 12.

[0099] The side cross-sectional view of the cast power inductor is as follows: Figure 2 shown.

[0100] The method for preparing the cast power inductor comprises the following steps:

[0101] (1) Blank preparation: The prefabricated powder is placed into a T-shaped mold of a preset size and hot-pressed, and then baked at 220°C to obtain a T-shaped base; the hot-pressing temperature is 180°C and the pressure is 450 MPa;

[0102] (1.1) Mixing a main powder and an auxiliary powder to obtain a composite soft magnetic alloy powder; wherein the D50 of the main powder is 39.84 μm, and the D50 of the auxiliary powder is 9.58 μm;

[0103] (1.2) mixing a binder, a curing agent, acetone, and the composite soft magnetic alloy powder obtained in step (1.1) to obtain a prefabricated powder;

[0104] (2) Winding the coil: Winding the enameled wire on the center column of the T-shaped base obtained in step (1), and bending the two end pins and attaching them to the bottom of the hem of the T-shaped base to obtain an assembly;

[0105] (3) Arrangement of the assembly: The assembly obtained in step (2) is arranged in an n×m matrix with equal spacing and pasted on a heat-sensitive adhesive film with an adhesion of 2000-3000 gf / 25 mm; wherein the spacing between the assemblies is 2 mm;

[0106] (4) Slurry pouring: a pouring mold is installed above the heat-sensitive adhesive film, and a magnetic slurry with a viscosity of 20,000 mPa.s is injected to obtain a second assembly; wherein the height of the pouring mold is greater than 1.2 mm of the inductor height; the raw materials of the magnetic slurry are calculated by weight as follows: 100 parts of composite soft magnetic alloy material, 4 parts of epoxy resin, 1.12 parts of ethylenediamine, and 3.60 parts of ethyl acetate;

[0107] (4.1) Mix epoxy resin and ethyl acetate and stir for 2 h to obtain an organic mixture;

[0108] (4.2) adding a composite soft magnetic alloy material to the organic mixture obtained in step (4.1), stirring for 10 hours, and obtaining a semi-finished soft magnetic alloy powder slurry; wherein the composite soft magnetic alloy material is a mixture of a first powder, a second powder, and a third powder; the D50 of the first powder is 146.8 μm, the D50 of the second powder is 49.6 μm, and the D50 of the third powder is 8.9 μm; and the mass ratio of the first powder, the second powder, and the third powder is 6:1:3;

[0109] (4.3) mixing and stirring ethylenediamine and the semi-finished soft magnetic alloy powder slurry obtained in step (4.2) for 30 minutes, and then vacuum degassing to obtain the magnetic slurry;

[0110] (5) Curing treatment: The second assembly obtained in step (4) is cured, demoulded and polished in sequence to obtain Figure 3 The inductor body shown in FIG. 1 includes a curing process comprising a first curing stage, a second curing stage, and a third curing stage performed sequentially; the first curing stage is performed at a temperature of 80° C. and a holding time of 4 hours; the second curing stage is performed at a temperature of 125° C. and a holding time of 1 hour; and the third curing stage is performed at a temperature of 180° C. and a holding time of 1 hour.

[0111] (6) Post-processing: Cutting, spraying, and electroplating the inductor blank obtained in step (5) in sequence to obtain the cast power inductor.

[0112] The size of the cast power inductor prepared in this embodiment is 2.5×2.0×1.0 mm.

[0113] The magnetic permeability of the magnetic slurry obtained in step (4) of this embodiment is tested at a frequency of f=1 MHz to be 32.8.

[0114] Example 2

[0115] This embodiment provides a cast power inductor, which is the same as that in the embodiment.

[0116] The method for preparing the cast power inductor differs from that of Example 1 only in that the weight ratio of the raw materials used in preparing the magnetic slurry in step (4) is changed to: 100 parts composite soft magnetic alloy material, 2.4 parts epoxy resin, 0.67 parts ethylenediamine, and 2.8 parts ethyl acetate. The magnetic permeability of the magnetic slurry was tested at a frequency of 1 MHz, and was 34.87.

[0117] Example 3

[0118] This embodiment provides a cast power inductor, which is the same as that in the embodiment.

[0119] The method for preparing the cast power inductor differs from that of Example 1 only in that the weight ratio of the raw materials used in preparing the magnetic slurry in step (4) is changed to: 100 parts composite soft magnetic alloy material, 6.0 parts epoxy resin, 1.68 parts ethylenediamine, and 4.6 parts ethyl acetate. The magnetic slurry exhibited a magnetic permeability of 31.2 at a frequency of f = 1 MHz.

[0120] In the preparation method provided in this embodiment, the temperature of the first stage curing in the curing treatment in step (5) is also changed to 100°C, and the holding time is changed to 2 hours; the temperature of the second stage curing is changed to 140°C, and the holding time is 1 hour; the temperature of the third stage curing is changed to 200°C, and the holding time is 1 hour.

[0121] Example 4

[0122] This embodiment provides a cast power inductor, which is the same as that in the embodiment.

[0123] The only difference between the preparation method of the cast power inductor and Example 1 is that: in this embodiment, the D50 of the first powder in step (4.2) is changed to 108.34 μm, the D50 of the second powder is changed to 28.86 μm, and the D50 of the third powder is changed to 4.2 μm; the mass ratio of the first powder, the second powder, and the third powder is 6:2:2.

[0124] The magnetic permeability of the magnetic slurry obtained in step (4) of this embodiment is tested at a frequency of f=1 MHz to be 28.84.

[0125] Example 5

[0126] This embodiment provides a cast power inductor, which is the same as that in the embodiment.

[0127] The only difference between the method for preparing the cast power inductor and Example 1 is that in this embodiment, the mass ratio of the first powder, the second powder, and the third powder in step (4) is changed to 6:3:1.

[0128] The magnetic permeability of the magnetic slurry obtained in step (4) of this embodiment is tested at a frequency of f=1 MHz to be 30.82.

[0129] Example 6

[0130] This embodiment provides a cast power inductor, which is the same as that in the embodiment.

[0131] The only difference between the preparation method of the cast power inductor and Example 1 is that in this example, the D50 of the first powder in step (4.2) is changed to 162.83 μm, the D50 of the second powder is changed to 54.69 μm, and the D50 of the third powder is changed to 10.84 μm.

[0132] The magnetic permeability of the magnetic slurry obtained in step (4) of this embodiment is tested at a frequency of f=1 MHz to be 38.45.

[0133] Example 7

[0134] This embodiment provides a cast power inductor, which is the same as that in the embodiment.

[0135] The method for preparing the cast power inductor differs from that of Example 1 only in that the weight ratio of the raw materials used in preparing the magnetic slurry in step (4) is changed to: 100 parts composite soft magnetic alloy material, 1.80 parts epoxy resin, 0.5 parts ethylenediamine, and 6.5 parts ethyl acetate. The magnetic permeability of the magnetic slurry was tested at a frequency of 1 MHz, and was 34.46.

[0136] Example 8

[0137] This embodiment provides a cast power inductor, which is the same as that in the embodiment.

[0138] The method for preparing the cast power inductor differs from that of Example 1 only in that the weight ratio of the raw materials used in preparing the magnetic slurry in step (4) is changed to: 100 parts composite soft magnetic alloy material, 8.40 parts epoxy resin, 2.35 parts ethylenediamine, and 6 parts ethyl acetate. The magnetic permeability of the magnetic slurry was tested at a frequency of f = 1 MHz and was 24.6.

[0139] The cast power inductors provided in Examples 1-8 were tested for size, inductance performance, and DC resistance. The results are shown in Table 1.

[0140] Table 1

[0141]

[0142] The cast power inductor provided in Example 6 of the present invention has excessive eddy current loss, small temperature rise current, and low inductance efficiency; the cast power inductor provided in Example 7 has weak bonding strength between the casting body and the assembly, resulting in product falling off; the cast power inductor provided in Example 8 has low magnetic permeability, resulting in the inductance value failing to meet the technical requirements.

[0143] In summary, the cast power inductor provided by the present invention is formed without pressure by pouring magnetic slurry, which prevents the coil from short-circuiting, breaking, or shifting to the edge of the inductor due to excessive pressure; it effectively improves the reliability of the inductor and the product yield.

[0144] The applicant declares that the above is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the scope of protection and disclosure of the present invention.

Claims

1. A cast power inductor, characterized in that: The cast power inductor comprises a T-shaped base, a hollow coil and a cast body; The base includes a hem and a center column; The center column is fixedly arranged at the center position of the hem; The hollow coil is tightly wound on the center column; The casting body is used to wrap the base and the hollow coil; The method for preparing the cast power inductor comprises the following steps: (1) Blank preparation: The prefabricated powder is placed into a T-shaped mold of a preset size and hot-pressed, and then baked to obtain a T-shaped base; (2) Winding the coil: Winding the enameled wire on the center column of the T-shaped base obtained in step (1), and bending the two end pins and fitting them to the bottom of the hem of the T-shaped base to obtain an assembly; (3) Arrangement of the assembly: The assembly obtained in step (2) is arranged at equal intervals in an n×m matrix and pasted on a thermal adhesive film; (4) Slurry casting: a casting mold is installed above the heat-sensitive adhesive film, and magnetic slurry is injected to obtain a second assembly; The preparation method of the magnetic slurry comprises: (4.1) Mix the epoxy resin and the organic solvent and stir for 1-3 hours to obtain an organic mixture; (4.2) Adding the composite soft magnetic alloy material to the organic mixture obtained in step (4.1), stirring for 4-12 hours, and obtaining a semi-finished soft magnetic alloy powder slurry; (4.3) mixing and stirring the curing agent and the semi-finished soft magnetic alloy powder slurry obtained in step (4.2) for 20-40 minutes, and then vacuum degassing to obtain the magnetic slurry; The composite soft magnetic alloy material in step (4.2) is a mixture of a first powder, a second powder and a third powder; The D50 of the first powder is 100-150 μm; The D50 of the second powder is 20-50 μm; The D50 of the third powder is 4-10 μm; (5) Curing treatment: curing, demoulding and polishing the second assembly obtained in step (4) to obtain an inductor blank; the curing includes first-stage curing, second-stage curing and third-stage curing performed in sequence; (6) Post-processing: The inductor blank obtained in step (5) is cut, sprayed, and electroplated in sequence to obtain the cast power inductor.

2. The cast power inductor according to claim 1, characterized in that: A wire groove is provided on one side of the hem.

3. The cast power inductor according to claim 1, characterized in that: The pins at both ends of the hollow coil are arranged at the bottom of the hem through wire grooves.

4. A method for preparing a cast power inductor according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) Blank preparation: The prefabricated powder is placed into a T-shaped mold of a preset size and hot-pressed, and then baked to obtain a T-shaped base; (2) Winding the coil: Winding the enameled wire on the center column of the T-shaped base obtained in step (1), and bending the two end pins and fitting them to the bottom of the hem of the T-shaped base to obtain an assembly; (3) Arrangement of the assembly: The assembly obtained in step (2) is arranged in an n×m matrix at equal intervals and pasted on a heat-sensitive adhesive film; (4) Slurry casting: a casting mold is installed above the thermal adhesive film, and magnetic slurry is injected to obtain a second assembly; The preparation method of the magnetic slurry comprises: (4.1) Mix the epoxy resin and the organic solvent and stir for 1-3 hours to obtain an organic mixture; (4.2) Adding the composite soft magnetic alloy material to the organic mixture obtained in step (4.1), stirring for 4-12 hours, and obtaining a semi-finished soft magnetic alloy powder slurry; (4.3) mixing and stirring the curing agent and the semi-finished soft magnetic alloy powder slurry obtained in step (4.2) for 20-40 minutes, and then vacuum degassing to obtain the magnetic slurry; The composite soft magnetic alloy material in step (4.2) is a mixture of a first powder, a second powder and a third powder; The D50 of the first powder is 100-150 μm; The D50 of the second powder is 20-50 μm; The D50 of the third powder is 4-10 μm; (5) Curing treatment: curing, demoulding and polishing the second assembly obtained in step (4) to obtain an inductor blank; the curing includes first-stage curing, second-stage curing and third-stage curing performed in sequence; (6) Post-processing: The inductor blank obtained in step (5) is cut, sprayed, and electroplated in sequence to obtain the cast power inductor.

5. The preparation method according to claim 4, characterized in that The method for preparing the prefabricated powder in step (1) comprises: (1.1) Mixing the main powder and the auxiliary powder to obtain composite soft magnetic alloy powder; (1.2) Mixing a binder, a curing agent, acetone, and the composite soft magnetic alloy powder obtained in step (1.1) to obtain a prefabricated powder.

6. The preparation method according to claim 5, characterized in that The main powder in step (1.1) includes any one of FeSiAl powder, FeSi powder or FeNi powder, or a combination of at least two of them.

7. The preparation method according to claim 5, characterized in that The D50 of the main powder in step (1.1) is 20-40 μm.

8. The preparation method according to claim 5, characterized in that The auxiliary powder in step (1.1) includes any one of FeSiAl powder, FeSi powder or FeNi powder, or a combination of at least two of them.

9. The preparation method according to claim 5, characterized in that The D50 of the auxiliary powder in step (1.1) is 2-10 μm.

10. The preparation method according to claim 4, characterized in that The temperature of the hot pressing molding in step (1) is 160-240°C.

11. The preparation method according to claim 4, characterized in that The pressure of the hot pressing molding in step (1) is 300-600 MPa.

12. The preparation method according to claim 4, characterized in that The baking temperature in step (1) is 180-260°C.

13. The preparation method according to claim 4, characterized in that The spacing between the assemblies in step (3) is 0.5-2 mm.

14. The preparation method according to claim 4, characterized in that The adhesion of the thermal adhesive in the thermal adhesive film in step (3) is 2000-3000 gf / 25 mm.

15. The preparation method according to claim 4, characterized in that The viscosity of the magnetic slurry in step (4) is 15000-25000 mPa.s.

16. The preparation method according to claim 4, characterized in that The raw materials of the magnetic slurry in step (4) include, by weight, 100 parts of composite soft magnetic alloy material, 2-8 parts of epoxy resin, 0.5-2.5 parts of curing agent, and 2-6 parts of organic solvent.

17. The preparation method according to claim 16, characterized in that The curing agent includes any one of ethylenediamine, diethylenetriamine, diethyltoluenediamine or dicyandiamide, or a combination of at least two of them.

18. The preparation method according to claim 16, characterized in that The organic solvent includes any one of ethyl acetate, n-propanol, isopropanol or ethanol, or a combination of at least two of them.

19. The preparation method according to claim 4, characterized in that The first powder includes any one of FeSiAl powder, FeSi powder, FeNi or amorphous powder, or a combination of at least two of them.

20. The preparation method according to claim 4, characterized in that The second powder includes any one of FeSiAl powder, FeSi powder, FeNi or amorphous powder, or a combination of at least two of them.

21. The preparation method according to claim 4, characterized in that The third powder includes any one of FeSiAl powder, FeSi powder, FeNi or amorphous powder, or a combination of at least two of them.

22. The preparation method according to claim 4, characterized in that The mass ratio of the first powder, the second powder and the third powder is 6:(1-3):(1-3).

23. The preparation method according to claim 19, characterized in that The amorphous powder includes FeSiBCr.

24. The preparation method according to claim 4, characterized in that In step (4), the height of the casting mold is 0.4-1.5 mm greater than the height of the inductor.

25. The preparation method according to claim 24, characterized in that In step (4), the height of the casting mold is 0.6-1.2 mm greater than the height of the inductor.

26. The preparation method according to claim 4, characterized in that The temperature of the first stage curing is 80-100°C.

27. The preparation method according to claim 4, characterized in that The holding time of the first stage curing is 2-4 hours.

28. The preparation method according to claim 4, characterized in that The temperature of the second stage curing is 120-140°C.

29. The preparation method according to claim 4, characterized in that The holding time of the second stage curing is 0.5-2h.

30. The preparation method according to claim 4, characterized in that The temperature of the third stage curing is 150-200°C.

31. The preparation method according to claim 4, characterized in that The heat preservation time of the third stage curing is 1-3 hours.

32. The preparation method according to claim 4, characterized in that The preparation method comprises the following steps: (1) Blank preparation: The prefabricated powder is loaded into a T-shaped mold of a preset size and hot-pressed, and then baked at 180-260°C to obtain a T-shaped base; wherein the hot-pressing temperature is 160-240°C and the pressure is 300-600 MPa; (1.1) Mixing a main powder and an auxiliary powder to obtain a composite soft magnetic alloy powder; wherein the D50 of the main powder is 20-40 μm, and the D50 of the auxiliary powder is 2-10 μm; (1.2) mixing a binder, a curing agent, acetone, and the composite soft magnetic alloy powder obtained in step (1.1) to obtain a prefabricated powder; (2) Winding the coil: Winding the enameled wire on the center column of the T-shaped base obtained in step (1), and bending the two end pins and fitting them to the bottom of the hem of the T-shaped base to obtain an assembly; (3) Arrangement of the assembly: The assembly obtained in step (2) is evenly spaced and arranged in an n×m matrix and pasted on a heat-sensitive adhesive film with an adhesion of 2000-3000 gf / 25 mm; wherein the spacing between the assemblies is 0.5-2 mm; (4) Slurry casting: a casting mold is installed above the thermal adhesive film, and a magnetic slurry with a viscosity of 15,000-25,000 mPa.s is injected to obtain a second assembly; wherein the height of the casting mold is greater than the height of the inductor by 0.4-1.5 mm; (4.1) Mix the epoxy resin and the organic solvent and stir for 1-3 hours to obtain an organic mixture; (4.2) Adding a composite soft magnetic alloy material to the organic mixture obtained in step (4.1) and stirring for 4-12 hours to obtain a semi-finished soft magnetic alloy powder slurry; wherein the composite soft magnetic alloy material is a mixture of a first powder, a second powder, and a third powder; the D50 of the first powder is 100-150 μm, the D50 of the second powder is 20-50 μm, and the D50 of the third powder is 4-10 μm; (4.3) mixing and stirring the curing agent and the semi-finished soft magnetic alloy powder slurry obtained in step (4.2) for 20-40 minutes, and then vacuum degassing to obtain the magnetic slurry; (5) Curing treatment: The second assembly obtained in step (4) is cured, demolded, and polished in sequence to obtain an inductor blank; wherein the curing treatment includes first-stage curing, second-stage curing, and third-stage curing in sequence; the temperature of the first-stage curing is 80-100°C, and the holding time is 2-4 hours; the temperature of the second-stage curing is 120-140°C, and the holding time is 0.5-2 hours; the temperature of the third-stage curing is 150-200°C, and the holding time is 1-3 hours; (6) Post-processing: The inductor blank obtained in step (5) is cut, sprayed, and electroplated in sequence to obtain the cast power inductor.

Citation Information

Patent Citations

  • Mold pouring molding wound inductor and preparation method thereof

    CN109036779A

  • Manufacturing method of integrally-formed inductor

    CN112397295A

  • Power inductor and preparation method thereof

    CN113963928A